Statin Treatment Induced a Lipogenic Expression Hierarchical Network Centered by SREBF2 in the Liver - Song, Shiyu; Niu, Mengyuan; Liang, Qiao; Wang, Lei; Min, Haiyan; Peng, Yuming; Wang, Hongwei; Gao, Qian (Frontiers in Endocrinology, 2021)
Statin treatment is a major prevention treatment for hypercholesterolemia and the management of patients with increased risk of cardiovascular disease (CVD) due to its protective effects. However, its long-term safety was questioned regarding its potential role in new-onset type 2 diabetes mellitus, and its effect on gene regulation in the liver is not yet fully understood. By reanalyzing the transcriptome of the livers of patients with obesity and hypercholesterolemia, this study shows a multiple module organization that is related to various clinical metabolic parameters and identified an expression hierarchical network involving cholesterol and fatty acid syntheses in the liver of statin-treated patients. The key genes of the network were validated by QPCR in the hepatocytes upon statin treatment. The upregulation of the key enzymes involving the synthesis of Acetyl-CoA and the induction of gentle global acetylation of pan-protein and histone H4 in hepatocytes were observed. The study provides an overall view of the statin effect on transcriptional and post-transcriptional regulation of genes in the liver.